(untitled) (Journal of the College of Basic Education, 2020)
Current search targets identify;. 1-The moral judgment of students with visual disabilities. 2- the significance of differences of moral judgment of students with visual disabilities by variables; A - degree of disability (blind - visually impaire). B) Sex (males – females). 3-The ego identity of students with visual disabilities. 4-Significance of Differences The identity of the ego among students with visual disabilities by variables. A - degree of disability (blind - visually impaired). B -Sex (males – females). 5-The nature of the relationship through the contribution of degrees of ego identity to the degree of moral judgment of students with visual disabilities. The current research is limited to students of Al-Noor Institute for the Blind (Blind - Visually Impaired) of Baghdad Governorate / Department of Special Needs Care in Baghdad / Karkh for morning studies for the academic year (2018/2019) and their ages are between 6-14 years. The sample (70) students and students, and to achieve the objectives of the research, the researcher has built two measures are the moral judgment and the identity of the ego darkened the characteristics of the psychometric and after the application of the measures showed the results as follows; 1-A high level of moral judgment among students with visual disabilities. 2-There are statistically significant differences in the level of moral judgment among students with visual disabilities according to variable (blind - visually impaired) and in favor of the visually impaired and may be due to loss of visual acuity. 3-There is no significant statistical difference in the level of moral judgment among students with visual disabilities according to the sex variable (male - female), the reason may be due to culture, society, customs and traditions because they live in the same environment. 4-An increase in the level of ego identity of pupils with visual disabilities. 5-There are no significant differences in the level of identity of the ego visually impaired (blind - visually impaired) according to the variable sex (male - female), may be due to culture community and customs and traditions because they live in the same environment. 6- The grades indicate a clear contribution and relation to the degrees of ego identity in degrees of moral judgment. Based on the results of the research, the researcher put a number of recommendations and proposals.